THE EFFECT OF TEACHER CERTIFICATION PROGRAMS AND EDUCATION AND TRAINING MODES ON IMPROVING PEDAGOGIC COMPETENCIES ON ELEMENTARY SCHOOL TEACHER IN DKI JAKARTA - Adhika Ganendra (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
Enhancing teacher competency is one of the factors that needs to be considered to improve the quality of education. As the effort to improve teacher competence, the government has certified and implemented teacher competency training since 2006. In 2015, the average score of the teacher competency test was only 56.69. Hence, the score based on teacher competency test become the background of this research. Further, as an evaluation of the certification program and the implementation of training on improving teacher competency proclaimed by the government. This study aims to determine the effect of teacher certification programs and training modes on improving the pedagogical competence of elementary school (SD) teachers in DKI Jakarta both partially and jointly. This research method uses a quantitative method approach with ANOVA variance analysis. The results showed that the teacher certification program and training mode policies were positively and significantly affected the partly or all in increasing the elementary school teacher pedagogical competencies in DKI Jakarta. As a suggestion from the results of this study, the government should include criteria for certification of educators in teacher recruitment because the increase in teacher pedagogical competence is strongly influenced by the certification program. In addition, the government should be selective in determining teacher training modes. It is proved that education and training by empowering teacher work groups or peers is more effective in improving teacher pedagogical competencies. Keywords: Teacher Certification, Pedagogic Competence, Teaching and Training Modes